The Effectiveness of Cognitive-Behavioral Counseling in Reducing Academic Procrastination Among Students - Setiawan, Gede Danu; Tasya, Amalia (Journal of Therapia, 2025)
Academic procrastination is one of the most prevalent behavioral issues affecting students’ academic achievement and psychological well-being. The voluntary delay of tasks despite anticipating negative consequences is associated with reduced academic performance, heightened stress, and decreased self-regulation. Addressing this challenge requires effective interventions grounded in empirical evidence. This study aims to evaluate the effectiveness of Cognitive-Behavioral Therapy (CBT) in reducing academic procrastination among students by synthesizing findings from experimental research, comparative studies, and literature reviews published between 2020 and 2025. Using a systematic literature review approach, data were retrieved from databases such as Consensus, Semantic Scholar, PubMed, and Google Scholar. The analysis included randomized controlled trials, quasi-experimental studies, and narrative reviews focusing on CBT, as well as comparative studies involving Acceptance and Commitment Therapy (ACT) and Mindfulness-Based Cognitive Therapy (MBCT). Twelve eligible articles were selected after rigorous screening, data extraction, and synthesis. Findings indicate that CBT consistently reduces procrastination behaviors across diverse educational settings, with both face-to-face and online formats demonstrating significant and lasting effects for two to four months. Comparisons reveal that ACT offers longer-term sustainability, while MBCT enhances positive academic emotions and optimism. Bibliometric trends show CBT’s dominance in scholarly attention between 2020 and 2025. These results underscore CBT’s role as a primary evidence-based intervention for reducing academic procrastination, while also highlighting the potential benefits of integrating CBT with ACT and MBCT. Practical implications include the adoption of hybrid counseling programs in schools and universities, supported by digital delivery systems to increase accessibility and long-term effectiveness